2010
DOI: 10.1016/j.wocn.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Pauses, gaps and overlaps in conversations

Abstract: This paper explores durational aspects of pauses, gaps and overlaps in three different conversational corpora with a view to challenge claims about precision timing in turn-taking. Distributions of pause, gap and overlap durations in conversations are presented, and methodological issues regarding the statistical treatment of such distributions are discussed. The results are related to published minimal response times for spoken utterances and thresholds for detection of acoustic silences in speech. It is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
394
8
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(432 citation statements)
references
References 41 publications
28
394
8
2
Order By: Relevance
“…We could show that in both datasets overlapping speech occurs frequently enough to be analyzed with a share of 18.9% for HHI and 12.3% for HCI. For the investigated HHI, this share is in-line with the results of other research groups [11], [33]. The amount of overlap in HCI is a bit lower but still sufficient.…”
Section: Discussionsupporting
confidence: 88%
“…We could show that in both datasets overlapping speech occurs frequently enough to be analyzed with a share of 18.9% for HHI and 12.3% for HCI. For the investigated HHI, this share is in-line with the results of other research groups [11], [33]. The amount of overlap in HCI is a bit lower but still sufficient.…”
Section: Discussionsupporting
confidence: 88%
“…However, estimates from psycholinguistic picture naming studies indicate that speakers need at least about 600 ms to plan a single word (Indefrey and Levelt, 2004) and much longer (about 1500 ms) to plan a simple sentence (Griffin and Bock, 2000). These figures are clearly much higher than the typical time between two turns at talk in conversation (e.g., Heldner and Edlund, 2010;Levinson and Torreira, 2015;Sacks et al, 1974). To respond with the quick timing typical of conversation (0-200 ms, e.g., Stivers et al, 2009), responders must therefore begin planning their responses while the previous turn is still unfolding.…”
Section: Introductionmentioning
confidence: 99%
“…ten Bosch et al (2005) found overlap to account for 44% of speaker changes in face-toface conversation. Heldner and Edlund (2010) report 40% of speaker-transitions involving overlaps. Only in Levinson and Torreira (2015) the proportion of overlap was clearly lower, with 30% of transitions occurring in overlap.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is almost perfectly consistent with previous research. Heldner and Edlund (2010), for example, report for overlap a mean length of 610 ms and a median length of 470 ms. The findings then support the view that ''the bulk of overlaps are of short duration'' (Levinson and Torreira 2015: 4; cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation